Development and validation of a culture-adapted observation protocol to measure students’ scientific practices in secondary biology classrooms: encompassing epistemic and non-epistemic dimensions - Zhao, Hui; Yu, Jian; Liu, Wencheng; Ma, Huangdong; Li, Gaofeng (Frontiers in Education, 2026)
IntroductionComprehensive assessments of scientific practices (SPs) require measuring both their epistemic and non-epistemic dimensions. However, existing classroom observation protocols systematically overlook non-epistemic practices; lack specificity, especially for secondary biology; have psychometric limitations, hindering holistic assessments of the proficiency of scientific practices; and less consideration given to cultural adaptability. This study aimed to develop and validate the Scientific Practices Observation Protocol (SPOP), which encompasses epistemic practices aligned with Next Generation Science Standards and non-epistemic practices, using the family resemblance approach.MethodsThe SPOP was validated using 883 students across 127 videotaped Grades 10–11 biology lessons in classrooms from diverse regions in China. Multi-dimensional Rasch measurement was employed to analyze dimensionality, validity, reliability, and measurement invariance.ResultsThe results confirmed a robust five-dimensional structure: investigating, sensemaking, critiquing, constraints, and interaction. The SPOP demonstrated strong psychometric properties, including excellent model fit, high reliability, and measurement invariance across gender, effectively capturing non-epistemic practices often overlooked by prior tools.DiscussionAs a culture-adapted psychometrically robust protocol that integrates both dimensions, the SPOP could equip educators with the ability to determine proficiency of scientific practices, support researchers in tracking the development of these practices, and provide a foundation for practice-oriented teaching reform.